Demographic Change in European Towns 2001–11: A Cross‐National Multi‐Level Analysis. (27th February 2017) - Smith, Ian
Abstract: The unique contribution of this paper is to empirically compare and contrast demographic change in settlements with a population between 5, 000 and under 50, 000 (defined as towns) across different national urban systems in Europe with common definitions for the first time. The analysis uses a new data set based on harmonised small area data and harmonised morphological definitions of what a town is. The paper hypothesises first that a general model of demographic growth can be applied across national urban systems and secondly that regional demographic change is a significant predictor of demographic change in towns nested within those regions within this generalised model. A fixed effect multi‐level regression analysis tests the importance of town‐level and regional factors among towns from five national systems but also within two individual national urban systems. The findings suggest that national context still matters and within some national systems, regional context also strongly predicts demographic change in towns.